Pregnancy outcomes following botulinum toxin type A exposure: A systematic review - Abdelkader, Noha; Arslan, Elif Keskin; Coskun, Hilal Erol-; Küçüksolak, Gözde; Kaplan, Yusuf Cem (International Journal of Scientific Research and Management (IJSRM), 2018)
Objective: To evaluate the available human data to-date in order to assess whether the prenatal exposure to botulinum toxin type A (BTX-A) is associated with major congenital malformations and other adverse pregnancy outcomes.Methods: Searches were conducted in PubMed/MEDLINE and Reprotox in November  2017. Cohort and case-control studies, case series, case reports were the primary data of interest.Results: No controlled studies but case series and case reports of therapeutic BTX-A administration during pregnancy were identified. Case reports regarding pregnant women with botulism were also reviewed.Conclusions: Limited data suggests that BTX-A exposure for therapeutic indications during pregnancy does not seem to be associated with an increase in risk of major congenital malformations. Rates of fetal loss were substantially different between prospective and retrospective data. Controlled epidemiological studies are needed to refute or support our findings.